Implementasi Pembelajaran Kitab Fathul Qorib dalam Meningkatkan Pemahaman Fiqih di MTs Al-Falahiyah Pondok Pesantren Langitan Widang Tuban - Habiburrohman, Habiburrohman; El-Yunusi, M. Yusron Maulana; Sulaiman, M. Sholehuddin (Lembaga Yasin AlSys, 2025)
Learning the book of fathul qorib is a learning process that is usually carried out in Islamic boarding schools and Islamic education institutions, especially at Langitan Islamic Boarding School. This book is one of the most popular books of fiqh, the work of Sheikh Muhammad bin Qosim al-Ghazi which is the sharah of the book of taqrib which is usually called matan abi syuja'. This research aims to reveal: 1) Improved understanding of Fiqh at MTs Al-Falahiyah. 2) Learning the Book of Fathul Qorib to Improve Understanding of Fiqh at MTs Al-Falahiyah. 3) Supporting and Inhibiting Factors for Learning the Book of Fathul Qorib in Increasing Understanding of Fiqh at MTs Al-Falahiyah. This research uses a descriptive qualitative approach. Data collection techniques were carried out using structured interviews, participant observation, and documentation. The results of the study on the implementation of learning the Fathul Qorib book in improving understanding of Islamic jurisprudence at MTs Al-Falahiyah, Langitan Widang Islamic Boarding School, Tuban showed that: 1) learning the Fathul Qorib book in improving understanding of Islamic jurisprudence went well and effectively, students' understanding of Islamic jurisprudence can be improved by studying the book. Fathul Qorib uses several methods, including muroja'ah and deliberation. 2) Learning the Fathul Qorib book at MTs Al-Falahiyah is realized well by implementing several varied methods, including classical, sorogan, wetonan, and lectures, teaching and learning activities of the book fathul qorib runs smoothly and effectively. 3) Supporting factors, such as teacher competence and appropriate learning methods can provide positive contributions to student understanding. However, there are also inhibiting factors that need to be addressed through evaluation and adjustment of strategies by teachers to continue to improve the process learning the book Fathul Qorib and overcoming existing obstacles.